Implementation of Sharia Principles in Canteng Koneng Batik Sumenep MSMEs in the Era of Industrial Revolution 4.0 - Dimas Wira Pandu; Dony Burhan Noor Hasan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Madura especially Sumenep, is a city that is still thick with its religion, therefore This study uses the concept of a marketing mix based on 4P sharia principles Product (produksi), pricing (harga), place (tempat), and promotion (promosi) - to determine whether or not the use of syariah principles in UMKM batik Canteng Koneng Sumenep within the context of Industry 4.0 has been successful. This study uses a kualitatif methodology. In order to gather information for this study, surveys, observations, and documentation are used. in addition to primary and secondary sources. Two people who have provided information are the proprietor of Canteng Koneng batik and their younger sibling. The study's findings show that Canteng Koneng batik adheres to sharia when it comes to using the 4P The product, price, place, and promotion mix is known as the marketing mix.